Unfairness in consumer services: Outcomes of differential treatment of new and existing clients - Teresa Fernandes (2016)
In a consumption context, there is a growing interest in understanding unfair behaviour of firms towards customers. Our research focuses on unfairness perceptions driven by differential treatment, particularly through price discrimination, i.e. the practice of charging differential prices to different customers. Our purpose is to investigate the consequences of these practices for unfairness perceptions, satisfaction, trust and patronage, showing a dual perspective: the perceptions of new vs existing clients when they face the advantaged or disadvantaged conditions. A survey-based experimental design approach was used. We conclude that unfairness perception is stronger for existing than for new clients, prompting negative attitudinal and behavioural consequences when the former are exposed to disadvantaged conditions in relation to the latter. Our study aims to provide marketers with a perspective on the pitfalls related to differential treatment between present and prospective clients, with implications in terms of design and implementation of customer management strategies.